Absence of glaucoma in DBA/2J mice homozygous for wild-type versions of Gpnmb and Tyrp1. - Howell, Gareth R.; Libby, Richard T.; Marchant, Jeffrey K.; Wilson, Lawriston A.; Cosma, Ioan M.; Smith, Richard S.; Anderson, Michael G.; John, Simon WM. (2016)
Background: The glaucomas are a common but incompletely understood group of diseases. DBA/2J mice develop a pigment liberating iris disease that ultimately causes elevated intraocular pressure (IOP) and glaucoma. We have shown previously that mutations in two genes, Gpnmb and Tyrp1, initiate the iris disease. However, mechanisms involved in the subsequent IOP elevation and optic nerve degeneration remain unclear.; Springer Open.